Peran Organisasi Perdagangan Dunia (WTO) dalam Menjaga Keseimbangan Ekonomi Indonesia - Addnan Nur Nasution; Adinda Arafah; Afriza Ulfa Ritonga; Ditiya Puspita; Rizqi Syahdila; Dwita Sakuntala (Universitas 45 Surabaya, 2025)
The World Trade Organization (WTO) plays a crucial role in maintaining Indonesia's economic balance. Through the implementation of fair and transparent international trade policies, the WTO helps enhance market access for Indonesian products and reduce trade barriers. Moreover, the WTO serves as a forum for trade negotiations and dispute resolution, ultimately contributing to the country's economic stability. This study analyzes the WTO's contributions to supporting Indonesia's economic growth through the oversight of trade agreements and dispute resolution. The findings show that Indonesia's active participation in the WTO has a positive impact on the national economic balance.